2017
DOI: 10.1371/journal.pone.0183827
|View full text |Cite
|
Sign up to set email alerts
|

Reduced proliferation of endothelial colony-forming cells in unprovoked venous thromboembolic disease as a consequence of endothelial dysfunction

Abstract: BackgroundVenous thromboembolic disease (VTD) is a public health problem. We recently reported that endothelial colony-forming cells (ECFCs) derived from endothelial cells (EC) (ECFC-ECs) from patients with VTD have a dysfunctional state. For this study, we proposed that a dysfunctional status of these cells generates a reduction of its proliferative ability, which is also associated with senescence and reactive oxygen species (ROS).Methods and resultsHuman mononuclear cells (MNCs) were obtained from periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Third, ECFCs’ angiogenic behavior is typically compromised in the presence of cardiovascular risk factors that predispose to the onset of ischemic disorders; this further contributes to discouraging the use of circulating ECFCs for autologous cell therapy [ 15 , 59 , 110 , 115 ]. For instance, the frequency and/or vasoreparative potential of circulating ECFCs are remarkably reduced with CAD [ 120 ], aging [ 121 ], diabetes [ 122 ], abdominal aortic aneurysm [ 123 ], venous thromboembolic disease [ 124 ], congenital diaphragmatic hernia [ 125 ], systemic lupus erythematosus [ 126 ], and the pediatric Moyamoya disease (MMD) [ 127 ]. In addition, ECFCs’ angiogenic behaviour is impaired in patients affected by human immunodeficiency virus (HIV), which has long been associated with cardiovascular disorders [ 128 ].…”
Section: Manipulation Of Pro-angiogenic Signaling Pathways To Imprmentioning
confidence: 99%
“…Third, ECFCs’ angiogenic behavior is typically compromised in the presence of cardiovascular risk factors that predispose to the onset of ischemic disorders; this further contributes to discouraging the use of circulating ECFCs for autologous cell therapy [ 15 , 59 , 110 , 115 ]. For instance, the frequency and/or vasoreparative potential of circulating ECFCs are remarkably reduced with CAD [ 120 ], aging [ 121 ], diabetes [ 122 ], abdominal aortic aneurysm [ 123 ], venous thromboembolic disease [ 124 ], congenital diaphragmatic hernia [ 125 ], systemic lupus erythematosus [ 126 ], and the pediatric Moyamoya disease (MMD) [ 127 ]. In addition, ECFCs’ angiogenic behaviour is impaired in patients affected by human immunodeficiency virus (HIV), which has long been associated with cardiovascular disorders [ 128 ].…”
Section: Manipulation Of Pro-angiogenic Signaling Pathways To Imprmentioning
confidence: 99%
“…An increased pro-inflammatory cytokines profile was also found in the supernatants of cultures of ECFC from VTD patients ( 36 ). Further studies showed that ECFC from patients with VTD exhibit reduced proliferation, increased senescence, increased levels of reactive oxygen species (ROS) and impaired expression of ephrin-B2/Eph-4 genes, markers of venous and arterial endothelium involved in vascular regeneration ( 37 ). The abnormal inflammatory response, increased oxidative-stress and senescence detected in ECFC from patients with VTD might contribute to a defective response of the endothelium to vascular injury in these patients, possibly leading to recurrent thrombotic events.…”
Section: Ecfc For the Investigation Of Endothelial Cell Biology In DImentioning
confidence: 99%
“…Furthermore, the authors found that ECFCs from VTE patients had an impaired ephrin-B2/Eph-4 gene transcription and enhanced oxidative stress with increased ROS, suggesting also a higher prothrombotic oxidation-related risk in these patient as compared to controls [ 33 ].…”
Section: The Complex Molecular Interplay Between the Three Componementioning
confidence: 99%